KINERJA BELAJAR, ADVERSITY INTELLIGENCE DAN SIKAP, TERHADAP NIAT BERWIRAUSAHA - Asfia Murni (Department of Management - Faculty of Business and Economics. Universitas Surabaya., 2009)
The university does not have competency to produce product which can absorbed by industry environment (Zulganef and Munabi, 2009), while the most wanted occupation by educated employee is as worker that give monthly compensation and very little (5%) that choose occupation or job as a entrepreneur after graduated from the university. The definition as entrepreneur as the man who has idea and man of action often related as the innovative or creative man factors than assumed could increase the entrepreneur, attitude, and personality (Me Cleland and David, 1987) and adversity intelligence (Stoltz, 2000) and the performance entrepreneurship study (Djamarah, 1994). The aims of the research: a) to analyze the performance of entrepreneurship study, adversity intelligence and attitude, with the intend of entrepreneur from the students; b) to examine and analyze the influence of performance of entrepreneurship study, adversity intelligence and the student attitude for entrepreneur aim. This research use multi regression analysis with 93 student respondent. The research shows that: a) The reaction of students to adversity intelligence, study report, attitude and intention of entrepreneur is high; b) There are simultan influence from adversity intelligence, the attitude of student to the intend of entrepreneur just show for the attitude, while for adversity intelligence and report study did not show its influence significantly.